2013
DOI: 10.2320/matertrans.mh201306
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Electrical Resistivity in Cold Rolled Ti Sheet

Abstract: Observation and evaluation of lattice defects such as vacancy, dislocation and grain boundary are very important for understanding microstructure development during thermo-mechanical treatments. Electrical resistivity measurements are superior to electron microscopies in terms of obtaining average information on micro-and nano-structures including lattice defects. The purpose of this study is to quantify lattice defects and crystallographic features in cold rolled and annealed pure Ti by precise measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[59] This is because in the bonded state, these effects are caused by an increase of lattice defects, such as dislocations, vacancies, and/or grain boundaries, as discussed earlier for deformed Cu [47] and Ti. [60] For example, in copper/ stainless steel clads, [19] an increase in the microhardness near the interface and free surfaces is observed due to cold plastic deformation. Microhardness (strain hardening) increases in the lower part of the base plate due to collisions with the anvil, whereas the microhardness increase in the upper part of the flyer plate is due to the sudden shock of the explosive charge detonation.…”
Section: Formation Of Severely Deformed Layers In Areas Near the Imentioning
confidence: 99%
See 1 more Smart Citation
“…[59] This is because in the bonded state, these effects are caused by an increase of lattice defects, such as dislocations, vacancies, and/or grain boundaries, as discussed earlier for deformed Cu [47] and Ti. [60] For example, in copper/ stainless steel clads, [19] an increase in the microhardness near the interface and free surfaces is observed due to cold plastic deformation. Microhardness (strain hardening) increases in the lower part of the base plate due to collisions with the anvil, whereas the microhardness increase in the upper part of the flyer plate is due to the sudden shock of the explosive charge detonation.…”
Section: Formation Of Severely Deformed Layers In Areas Near the Imentioning
confidence: 99%
“…The effect of the <111> and <100> fiber-type texture formation on the electrical resistivity of copper wires has been discussed by Pavithra et al [62] and Moisy [47] and they found no significant effect. On the other hand, Ueda et al [60] showed that the electrical resistivity of cold-rolled cp-Ti is dependent on the formation of specific texture components. They reported that the resistivity along the c-axis of Ti was higher than that along other axes.…”
Section: Formation Of Severely Deformed Layers In Areas Near the Imentioning
confidence: 99%
“…On the other hand, the resistivity at 300 K, ρ 300 , increased with true strain up to ε t = 0.4, and then decreased before increasing again. This characteristic change in ρ 300 is most likely due to the developed texture 13 . These increases can be attributed to lattice defects introduced by the cold rolling.…”
Section: Determination Of Matthiessen's Empirical Relationshipmentioning
confidence: 99%